Exploration of Supporting Factors for Achieving Academic Achievement in Doctoral Programs in Higher Education - Hariyati, Nunuk; Riyanto, Yatim; Khamidi, Amrozi; Wulandari, Ayu; Islamiah, Nia; Sayeed, Raihand Ramadhani Abdul (FKIP Universitas Lampung, 2024)
Exploration of Supporting Factors for Achieving Academic Achievement in Doctoral Programs in Higher Education. The demands of change with the dynamics of global issues, one of which is the Sustainable Development Goals (SDGs), embody the role of Higher Education in producing competitive Human Resources. In-depth identification of academic supporting factors that influence the achievement of PLO (Program Learning Outcomes) needs to be done to determine strategic efforts in organizing education in the realm of study programs to produce competent and reliable graduates, especially for the doctoral program in Educational Management. Objectives: This study aims to explore academic supporting factors in the Doctoral Program in Educational Management at Surabaya State University (UNESA) to produce a description of academic support with the dynamics of the factors that influence it. Methods: This study used a descriptive quantitative approach with Exploratory Factor Analysis (EFA) with Jamovi Application to identify the underlying structure of a set of academic supporting variables, both from students as individuals and institutional factors. The data in this study were collected using a questionnaire instrument distributed to 75 students. Findings: The research results show that 3 factors are academic support factors in the UNESA Educational Management Doctoral Study Program, namely (1) Support System and Social Environment, (2) Learning Motivation, (3) Self-regulation. Conclusion: from the results it is interpreted that the realization of Doctoral Program students in Educational Management who can fulfil their lecture assignments and complete their studies on time is influenced by factors originating from external (support system and social environment) and internal factors (learning motivation and self-regulation). Keywords: academic, supporting factor, higher education.DOI: http://dx.doi.org/10.23960/jpp.v14.i3.2024111